La distopia nel paese delle utopie finisce l’era di Trump - Mamoli Zorzi , Rosella (Oltreoceano - Rivista sulle migrazioni, 2022)
L’assalto del 6 gennaio al Campidoglio di Washington termina la distopia di Trump: il paese rimane diviso e lo fu in passato con la Guerra Civile. Utopia e distopia si riferiscono a testi letterari. L’America è stata sempre la terra delle utopie, come realtà e come testi: si esaminerà il rapporto tra testi e realtà. Dystopia in the Country of Utopias: the Ending of Trump's Administration The Washington Capitol assault of 6 January 2021 has concluded Trump's administration: the country is still divided as it was in the past with the Civil War. Utopia and dystopia refer to literary texts. America has always been the country of utopias, both in reality and in literary texts: this paper will deal with the relationship between literary texts and reality.